Preparation method of PVDF-Q-ZIF-67 / POTS film and application of PVDF-Q-ZIF-67 / POTS film in treatment of radioactive waste liquid of nuclear power station
By preparing PVDF-Q-ZIF-67/POTS membranes, combined with electrospinning and spraying technology, the problem of complex and low efficiency of membrane distillation process in radioactive waste liquid treatment of nuclear power plants is solved, efficient nuclide separation and concentration is achieved, and the membrane life is extended.
Patent Information
- Application Number
- CN202510276375.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-06-10
AI Technical Summary
The prior art When treating radioactive waste liquid of nuclear power plants, the membrane distillation process is complex, low efficiency and high cost. In addition, the Janus porous membrane is prone to droplet transmission obstacles when treating radioactive wastewater, which reduces the membrane life.
The PVDF-Q-ZIF-67/POTS film was prepared by electrospinning, and the PVDF-Q hydrophilic layer was sprayed on the PVDF base film, and the ZIF-67/POTS superhydrophobic coating was sprayed on the PVDF base film, and the synthetic film was assembled layer by layer to achieve the combination of superhydrophobicity and hydrophilicity.
It improves the film's anti-pollution and mechanical properties, extends the service life of the film, and achieves efficient nuclide separation and concentration, and has stable membrane flux and high nuclide retention rate.
Smart Images

Figure CN120115002A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the fields of radioactive wastewater treatment and membrane preparation technology, and particularly relates to a preparation method of a PVDF-Q-ZIF-67 / POTS membrane and its application in treating radioactive waste liquid from nuclear power plants. Background Art
[0002] Low-level radioactive wastewater is generated in each link of the nuclear fuel nuclear cycle, such as uranium-containing low-level radioactive wastewater generated by uranium conversion and purification, acid-containing low-level radioactive wastewater from nuclear power plants, etc. These wastewaters not only contain radioactive nuclides but also contain various inorganic and organic pollutants. If not properly treated, they will cause great harm to the environment and humans. At present, although such wastewaters have been treated and disposed of relatively effectively, there are still problems such as complex treatment processes, low efficiency, and high costs.
[0003] Membrane distillation is a new membrane separation technology that drives steam permeation by the steam pressure difference on both sides of a microporous hydrophobic membrane. It can effectively remove pollutants such as dissolved solids, organic matter, and heavy metal ions in sewage, thereby achieving efficient sewage treatment and water quality improvement.
[0004] However, membrane wetting, fouling, and scaling are the key problems restricting the development of membrane distillation. Compared with traditional hydrophobic membranes, composite Janus membranes have a special asymmetric structure and better membrane distillation performance. They show great application potential in cooperative or independent working modes and can achieve functions that traditional membranes cannot. Currently, they have been widely studied in fields such as oil-water separation and seawater desalination. However, due to the presence of various ions and substances in the radioactive waste liquid from nuclear power plants, when the Janus porous membrane is used for radioactive wastewater treatment, some substances will infiltrate the hydrophobic layer of the Janus porous membrane, hindering the transport of droplets and reducing the membrane life.
[0005] Quercetin has a Π-bond conjugated system and multiple phenolic hydroxyl groups, which can provide oxygen atoms to attract metal ions close to the electron-dense region around it and form coordination compounds with metal ions or trace elements, ensuring the safety of metal ions. Therefore, adding Quercetin to electrospun fibers can improve the anti-fouling property of the membrane. In addition, the presence of phenolic hydroxyl groups and double bonds in Quercetin endows it with good antibacterial and chemical stability, which can enhance the mechanical properties of electrospun fibers.
[0006] Metal-organic framework materials (MOFs) are a class of periodic reticular framework porous crystals formed by self-assembly based on inorganic metal ions or metal clusters as nodes and organic ligands as centers through coordination. They have adjustable pore sizes, high specific surface areas, and excellent chemical properties. ZIF-67 is one of the widely used MOF materials. It uses cobalt ions as the metal center and 2-methylimidazole as the bridging ligand, and is constructed through a biomimetic zeolite topology. It has good thermal and chemical stability, adjustable pore size, etc., and has broad application prospects. ZIF-67 can be used to prepare superhydrophobic membranes to improve the nuclide separation efficiency and the life of the membrane, thereby further optimizing the waste liquid treatment process and having important value in the treatment of radioactive wastewater. Summary of the Invention
[0007] An object of the present invention is to solve at least the above problems and / or defects and provide at least the advantages described hereinafter.
[0008] To achieve these objects and other advantages of the present invention, a method for preparing a PVDF-Q-ZIF-67 / POTS membrane is provided, including the following steps:
[0009] Step 1: Add polyvinylidene fluoride (PVDF) to dimethylacetamide (DMAC) and stir until completely dissolved to obtain a PVDF solution; add polyvinyl alcohol (PVA) and quercetin (Que) to dimethyl sulfoxide (DMSO) and stir until completely dissolved to obtain a PVA solution. Mix the two solutions, stir and then perform electrospinning to obtain a PVDF-Q hydrophilic layer, and dry it.
[0010] Step 2: Immerse the PVDF-Q hydrophilic layer in a mixed solution for crosslinking, then rinse with deionized water and dry.
[0011] Step 3: Dissolve LiCl in DMAC, then add PVDF and stir until completely dissolved. Let it stand for defoaming to form a spinning solution, and obtain a PVDF-based membrane after electrospinning.
[0012] Step 4: Prepare a ZIF-67 / 1H,1H,2H,2H-perfluorooctyltriethoxysilane (POTS) superhydrophobic coating solution, and spray the solution on the surface of the polyvinylidene fluoride-based membrane using a spray gun to form a ZIF-67 / POTS superhydrophobic coating.
[0013] Step 5: Synthesize a PVDF-Q-ZIF-67 / POTS membrane by layer-by-layer assembly of the PVDF-Q hydrophilic layer and the PVDF-based membrane sprayed with the ZIF-67 / POTS superhydrophobic coating.
[0014] Preferably, in the first step, the mass of PVDF accounts for 11-13 wt% of the PVDF solution system, the mass of DMAC accounts for 87-89 wt% of the PVDF solution system, the mass of PVA accounts for 15-18 wt% of the PVA solution system, the mass of Que accounts for 3-8 wt% of the PVA solution system, and the mass of DMSO accounts for 74-82 wt% of the PVA solution system.
[0015] Preferably, in the first step, magnetic stirring is used for all stirrings, the stirring speed is 400-600 r / min, the stirring temperature is 60-80 °C, the mass ratio of the PVDF solution to the PVA solution is 6-7:3-4, and the stirring time is 2-4 h.
[0016] Preferably, in the first step, the conditions for electrospinning are: voltage -2.4 / 20 KV, the distance from the metal needle of the syringe to the electrospinning drum is 20-24 cm, the drum rotation speed is 60-80 r / min, the injection speed is 0.1-0.2 mm / min, the temperature is 27±3 °C, the translation range is 120 cm, the drying temperature is 60-80 °C, and the drying time is 1 h.
[0017] Preferably, in the second step, the mixed solution is composed of a 25% glutaraldehyde (GA) solution, citric acid (CA), and deionized water, and the mass ratio of the three is 0.1-0.3:1.2-1.3:96.5-98.5, the crosslinking time is 2 h, and it is rinsed with deionized water 2-3 times; the drying oven temperature is 60-80 °C, and the drying time is 1-2 h.
[0018] Preferably, in the third step, the mass of LiCl accounts for 0.1-0.2 wt% of the entire solution system, the mass of PVDF accounts for 10-11 wt% of the entire solution system, the mass of DMAC accounts for 88.8-88.9 wt% of the entire solution system, magnetic stirring is used, the stirring speed is 400-800 r / min, and the stirring temperature is 60-70 °C.
[0019] Preferably, in the third step, the conditions for electrospinning are: voltage -2.4 / 28 KV, the distance from the metal needle of the syringe to the electrospinning drum is 20-24 cm, the drum rotation speed is 60-80 r / min, the injection speed is 0.06-0.1 mm / min, the temperature is 27±3 °C, and the translation range is 120 cm.
[0020] Preferably, in the fourth step, the preparation method of the ZIF-67 / POTS superhydrophobic coating solution is as follows: Cobalt nitrate hexahydrate is dissolved in anhydrous methanol and shaken until completely dissolved to form a 0.1 mol / L solution. 2-Methylimidazole is dissolved in anhydrous methanol and shaken until completely dissolved to prepare a 0.4 - 0.6 mol / L solution. Then, the 2-methylimidazole solution is slowly poured into the cobalt nitrate solution according to the molar ratio of cobalt ions to 2-methylimidazole of 1:4 - 6. After stirring at 25°C for 1 h, the resulting milky suspension is collected and centrifuged at a speed of 8000 - 10000 rpm for 8 - 10 min. The white precipitate obtained by centrifugation is washed 3 times with methanol and dried in an oven at 70 - 80°C overnight to obtain ZIF-67 powder. POTS is added to 40 ml of ethanol and stirred for 2 h, then ZIF-67 powder is added and stirred for 30 min. The molar ratio of ZIF-67 to POTS is 1:1. After ultrasonic treatment for 40 min, the ZIF-67 / POTS superhydrophobic coating solution is obtained.
[0021] Preferably, in the fourth step, the conditions for spraying the prepared solution are as follows: The PVDF substrate film is soaked in ethanol for 2 h and then dried. The spray gun is wetted with a small amount of methanol for pre-spraying. The PVDF substrate film is placed at an angle of 30° to the horizontal plane. The spray gun nozzle is perpendicular to the film and the distance is 15 cm. The spraying speed is 0.5 mm / s. After each spraying, the film is placed in an oven at 70°C for 15 min, and this is repeated 3 times. Finally, the film is placed in an oven at 70°C and dried overnight.
[0022] The present invention also provides an application of the PVDF-Q-ZIF-67 / POTS membrane in treating radioactive waste liquid from nuclear power plants. The specific method is as follows: The radioactive waste liquid is pumped into a direct contact membrane distillation device using the PVDF-Q-ZIF-67 / POTS membrane for membrane distillation. Using the temperature difference between both sides of the membrane material as the driving force, a concentrated solution is obtained, and the distillate is condensed and collected, completing the concentration of the radioactive wastewater and the separation of radionuclides. In the direct contact membrane distillation device, the feeding temperature of the radioactive waste liquid is set at 70 - 80°C, the feeding and discharging flow rates are 100 rpm, the permeate is 200 ml of pure water, and the condensation temperature is 25°C. The radioactive waste liquid is heated from room temperature to the feeding temperature required for membrane distillation. The heat energy comes from the waste heat utilization system of the nuclear power plant reactor, and the recovery method is one of a heat pump, a recuperator, and a heating furnace, without the need for additional heating.
[0023] The present invention has at least the following beneficial effects:
[0024] (1) The PVDF-Q-ZIF-67 / POTS membrane provided by the present invention has superhydrophobicity on one side and hydrophilicity on the other side. The present invention includes a PVDF-Q hydrophilic nanofiber membrane, a PVDF nanofiber base membrane, and a ZIF-67 / POTS superhydrophobic coating. By combining a variety of materials with different properties to prepare the PVDF-Q-ZIF-67 / POTS membrane, the PVDF-Q-ZIF-67 / POTS membrane has different properties in the thickness direction, which can avoid the infiltration of various substances and ions in radioactive wastewater into the membrane, increasing the service life of the membrane;
[0025] (2) The present invention uses the electrospinning method to prepare the PVDF-Q-ZIF-67 / POTS membrane, which has the advantages of adjustable pore size and large specific surface area. In the PVDF-Q-ZIF-67 / POTS membrane, the hydrophilic layer can shorten the distance of vapor transmission, reduce the mass transfer resistance, improve the membrane flux and mechanical properties. The addition of Quercetin makes the anti-fouling property and mechanical properties of the membrane better. Compared with the PVDF base membrane, the PVDF-Q-ZIF-67 / POTS membrane has a higher membrane flux and rejection rate;
[0026] (3) A superhydrophobic membrane for nuclide separation is designed based on the ZIF-67 material, which has a large specific surface area, abundant pores and an adjustable framework structure, providing a promising new strategy for the preparation of superhydrophobic membranes;
[0027] (4) The PVDF-Q-ZIF-67 / POTS membrane provided by the present invention is applied to the direct contact membrane distillation (DCMD) technology, which can effectively separate nuclides in radioactive waste liquid. The membrane flux can be maintained stable for a long time, with a high concentration multiple and a nuclide rejection rate ≥ 99.9%;
[0028] Other advantages, objectives and features of the present invention will be partially reflected by the following description and partially understood by those skilled in the art through the research and practice of the present invention. Description of the Drawings
[0029] Figure 1 It is the chemical structure diagram of Quercetin used in the present invention;
[0030] Figure 2 It is the contact angle comparison diagram of the hydrophilic layer and the superhydrophobic layer of the PVDF-Q-ZIF-67 / POTS membrane prepared in Example 1 of the present invention;
[0031] Figure 3 It is the structural schematic diagram of the flat membrane module for directly cooling the permeate of the present invention;
[0032] Figure 4 It is the radioactive waste liquid treatment device diagram established for the flat membrane module for directly cooling the permeate;
[0033] Figure 5 It is the data graph of membrane flux, rejection rate and conductivity in Application Example 1 of the present invention;
[0034] Figure 6 It is the data graph of membrane flux, rejection rate and conductivity in Application Example 2 of the present invention;
[0035] Figure 7 It is the data graph of membrane flux, rejection rate and conductivity in Comparative Example 1 of the present invention;
[0036] Figure 8 It is the data graph of membrane flux and conductivity in Comparative Example 2 of the present invention;
[0037] Figure 9 It is the comparison graph of rejection rates in Application Example 2 and Comparative Example 2 of the present invention;
[0038] Figure 10 It is the data graph of membrane flux, rejection rate and conductivity in Comparative Example 3 of the present invention;
[0039] Figure 11 It is the data graph of membrane flux and rejection rate in Comparative Example 4 of the present invention;
[0040] Figure 12 It is the data graph of membrane flux and rejection rate in Comparative Example 5 of the present invention. Detailed implementation manners
[0041] The following further elaborates on the present invention in conjunction with the attached drawings, so that those skilled in the art can implement it with reference to the text of the specification.
[0042] Example 1
[0043] This example provides a preparation method of a PVDF-Q-ZIF-67 / POTS membrane, including the following steps:
[0044] Step 1: Add 22 g of PVDF into a beaker containing 178 g of DMAC, and magnetically stir at 60 °C at 400 r / min for 2 h until completely dissolved to obtain a PVDF solution; add 1 g of PVA and 0.2 g of Que (whose chemical structure is as Figure 1As shown, it was placed in 5.47 g of DMSO and magnetically stirred at 400 r / min at 60 °C for 2 h until completely dissolved to obtain a PVA solution; the PVDF solution and the PVA solution were mixed and magnetically stirred at 400 r / min at 60 °C for 2 h, and a PVDF-Q hydrophilic layer was obtained by electrospinning. The PVDF-Q hydrophilic layer was placed in an oven at 60 °C and dried for 1 h. Among them, the conditions for electrospinning were: voltage -2.4 / 20 KV, the distance from the metal needle of the syringe to the electrospinning drum was 20 cm, the drum rotation speed was 60 r / min, the injection speed was 0.1 mm / min, the temperature was 27 ± 3 °C, the translation range was 120 cm, the drying temperature was 60 °C, and the drying time was 1 h.
[0045] Step 2: Mix 1.2 g of GA, 4.8 g of CA, and 394 g of deionized water to form a mixed solution. Then immerse the PVDF-Q hydrophilic layer in the mixed solution for crosslinking for 2 h, rinse it 3 times with deionized water, and place it in an oven at 60 °C and dry for 1 h.
[0046] Step 3: Dissolve 0.2 g of LiCl in 177.8 g of DMAC, then add 22 g of PVDF, and magnetically stir at 400 r / min at 60 °C for 2 h until completely dissolved. Let it stand for defoaming to form a spinning solution, and a PVDF base film was obtained after electrospinning. Among them, the conditions for electrospinning were: voltage -2.4 / 28 KV, the distance from the metal needle of the syringe to the electrospinning drum was 20 cm, the drum rotation speed was 60 r / min, the injection speed was 0.06 mm / min, the temperature was 27 ± 3 °C, and the translation range was 120 cm.
[0047] Step 4: Prepare the ZIF-67 / POTS superhydrophobic coating solution. First, dissolve 2.91 g of cobalt nitrate hexahydrate in 100 ml of anhydrous methanol and shake until completely dissolved to form a 0.1 mol / L solution. Dissolve 4.93 g of 2-methylimidazole in 100 ml of anhydrous methanol and shake until completely dissolved. Then slowly pour the 2-methylimidazole solution into the cobalt nitrate solution, stir at 25 °C for 1 h, collect the resulting milky suspension, and centrifuge at 8000 rpm for 10 min. Wash the centrifuged white precipitate with methanol three times and dry it in an oven at 70 °C overnight to obtain ZIF-67. Then add 0.448 g of POTS to 40 ml of ethanol and stir for 2 h, add 0.196 g of ZIF-67 powder and stir for 30 min, and ultrasonicate for 40 min to obtain the ZIF-67 / POTS superhydrophobic coating solution. Finally, soak the PVDF substrate film in ethanol for 2 h and dry it. Wet the spray gun with a small amount of methanol for pre-spraying. Pour the ZIF-67 / POTS superhydrophobic coating solution into the spray gun. Place the PVDF substrate film at an angle of 30° to the horizontal plane. The spray gun nozzle is perpendicular to the film and 15 cm away. The spraying speed is 0.5 mm / s. After each spraying, place the film in an oven at 70 °C for 15 min and repeat three times to form a ZIF-67 / POTS superhydrophobic coating on the surface of the PVDF substrate film, and dry the film in an oven at 70 °C overnight.
[0048] Step 5: Synthesize the PVDF-Q-ZIF-67 / POTS membrane by layer-by-layer assembly of the PVDF-Q hydrophilic layer and the PVDF substrate film sprayed with the ZIF-67 / POTS superhydrophobic coating. Figure 2 Figure for the comparison of the contact angles of the hydrophilic layer and the superhydrophobic layer of the PVDF-Q-ZIF-67 / POTS membrane. As Figure 2 can be seen, the prepared PVDF-Q-ZIF-67 / POTS membrane has superhydrophobicity.
[0049] Application Example 1
[0050] Use the PVDF-Q-ZIF-67 / POTS membrane prepared in Example 1 to simulate the application of radioactive waste liquid in nuclear power plants, including the following steps:
[0051] Simulate 500 mL of radioactive waste liquid containing 0.01 mol / L oxalic acid, 0.005 mol / L citric acid, 1 g / L potassium permanganate, 10 mg / L strontium, and 10 mg / L cobalt in a nuclear power plant as the feed liquid, and conduct a direct contact membrane distillation experiment in the radioactive waste liquid treatment device as Figure 4 shown; first, heat the feed liquid to 80 °C using the waste heat of the nuclear power plant reactor, and then pump the feed liquid into the device as Figure 3The hot-side cavity of the flat membrane module shown, the permeate is input into the cold-side cavity of the flat membrane module through peristaltic pump B. Driven by the vapor pressure difference between the hot side and the cold side, the feed liquid evaporates on the membrane surface of the hot-side cavity and transfers heat and mass to the cold side, thereby increasing the distillate.
[0052] Among them, the feed and discharge flow rates are 100 rpm, the permeate is 200 ml of pure water, the condensation temperature is 25 °C, the membrane flux, rejection rate and conductivity are measured, and the test results are as Figure 5 shown.
[0053] The results show that during the process of treating radioactive waste liquid containing 0.01 mol / L oxalic acid, 0.005 mol / L citric acid, 1 g / L potassium permanganate, 10 mg / L strontium, and 10 mg / L cobalt in a nuclear power plant with the obtained PVDF-Q-ZIF-67 / POTS membrane, the membrane flux of PVDF-Q-ZIF-67 / POTS can be maintained stable for a long time, the concentration multiple is 10 times, and the nuclide rejection rate ≥ 99.9%, indicating that the PVDF-Q-ZIF-67 / POTS membrane has excellent anti-wetting performance and durability.
[0054] Application Example 2
[0055] This example uses the PVDF-Q-ZIF-67 / POTS membrane prepared in Example 1 to simulate the application of radioactive laundry wastewater containing uranium in a nuclear power plant, including the following steps:
[0056] Simulate 500 mL of radioactive laundry wastewater containing 60 mg / L sodium dodecyl sulfate, 200 mg / L machine oil, 100 mg / L sodium oleate, and 10 mg / L uranium in a nuclear power plant, and use it as the feed liquid. In the radioactive waste liquid treatment device as shown in Figure 4 conduct a direct contact membrane distillation experiment; first heat the feed liquid to 80 °C using the waste heat of the nuclear power plant reactor, then pump the feed liquid into the hot-side cavity of the flat membrane module through peristaltic pump A, and input the permeate into the cold-side cavity of the flat membrane module through peristaltic pump B. Driven by the vapor pressure difference between the hot side and the cold side, the feed liquid evaporates on the membrane surface of the hot-side cavity and transfers heat and mass to the cold side, thereby increasing the distillate.
[0057] Among them, the feed and discharge flow rates are 100 rpm, the permeate is 200 ml of pure water, the condensation temperature is 25 °C, the membrane flux, rejection rate and conductivity are measured, and the test results are as Figure 6 shown.
[0058] The results show that during the treatment of radioactive laundry wastewater containing 60 mg / L sodium dodecyl sulfate, 200 mg / L machine oil, 100 mg / L sodium oleate, and 10 mg / L uranium in a nuclear power plant with the obtained PVDF-Q-ZIF-67 / POTS membrane, the membrane flux of the PVDF-Q-ZIF-67 / POTS membrane can remain stable for a long time, the concentration multiple is 8.3 times, and the nuclide rejection rate is ≥99.9%, indicating that the PVDF-Q-ZIF-67 / POTS membrane has excellent anti-wetting and anti-pollution properties.
[0059] Comparative Example 1 (different from Example 1: only step three is carried out, that is, only the PVDF-based membrane is used)
[0060] Dissolve 0.2 g of LiCl in 177.8 g of DMAC, then add 22 g of PVDF, and magnetically stir at 400 r / min at 60 °C for 2 h until completely dissolved. Let it stand for defoaming to form a spinning solution, and obtain a PVDF-based membrane after electrospinning. The conditions for electrospinning are: voltage 2.4 / 14.5 KV, the distance from the metal needle of the syringe to the electrospinning drum is 16 cm, the drum rotation speed is 30 r / min, the injection speed is 0.15 mm / min, the temperature is 27 °C, and the translation range is 120 cm.
[0061] Using the PVDF-based membrane, 500 mL of radioactive waste liquid containing 0.01 mol / L oxalic acid, 0.005 mol / L citric acid, 1 g / L potassium permanganate, 10 mg / L strontium, and 10 mg / L cobalt in a nuclear power plant is used as the feed liquid, and the membrane distillation experiment is carried out according to the method of Application Example 1, and the membrane flux, rejection rate, and conductivity are measured. The test results are as Figure 7 shown.
[0062] The results show that during the treatment of radioactive waste liquid containing 0.01 mol / L oxalic acid, 0.005 mol / L citric acid, 1 g / L potassium permanganate, 10 mg / L strontium, and 10 mg / L cobalt in a nuclear power plant with the PVDF-based membrane, the membrane flux of the PVDF-based membrane is lower than that of the PVDF-Q-ZIF-67 / POTS membrane, and the conductivity increases, indicating that the PVDF-Q-ZIF-67 / POTS membrane improves the membrane flux and has durability.
[0063] Comparative Example 2 (different from Example 1: Que is not added in step one, and the others are carried out according to Example 1 to obtain the PVDF-ZIF-67 / POTS membrane)
[0064] Step 1: Dissolve 22 g of PVDF in a beaker containing 178 g of DMAC, and stir magnetically at 400 r / min for 2 h at 60 °C until completely dissolved to obtain a PVDF solution; place 1 g of PVA in 5.47 g of DMSO, and stir magnetically at 400 r / min for 2 h at 60 °C until completely dissolved to obtain a PVA solution; mix the two solutions of PVDF solution and PVA solution, stir magnetically at 400 r / min for 2 h at 60 °C, and obtain a PVDF layer by electrospinning. Place the PVDF layer in an oven at 60 °C and dry for 1 h. Among them, the conditions for electrospinning are: voltage -2.4 / 20 KV, the distance from the metal needle of the syringe to the electrospinning roller is 20 cm, the roller speed is 60 r / min, the injection speed is 0.1 mm / min, the temperature is 27 ± 3 °C, the translation range is 120 cm, the drying temperature is 60 °C, and the drying time is 1 h.
[0065] Step 2: Mix 1.2 g of GA, 4.8 g of CA, and 394 g of deionized water to form a mixed solution, then immerse the PVDF layer in the mixed solution for crosslinking for 2 h, rinse it 3 times with deionized water, and dry it in an oven at 60 °C for 1 h.
[0066] Step 3: Dissolve 0.2 g of LiCl in 177.8 g of DMAC, then add 22 g of PVDF, stir magnetically at 400 r / min for 2 h at 60 °C until completely dissolved, stand for defoaming to form a spinning solution, and obtain a PVDF-based membrane after electrospinning. Among them, the conditions for electrospinning are: voltage -2.4 / 28 KV, the distance from the metal needle of the syringe to the electrospinning roller is 20 cm, the roller speed is 60 r / min, the injection speed is 0.06 mm / min, the temperature is 27 ± 3 °C, and the translation range is 120 cm.
[0067] Step 4: Prepare the ZIF-67 / POTS superhydrophobic coating solution. First, dissolve 2.91 g of cobalt nitrate hexahydrate in 100 ml of anhydrous methanol and shake until completely dissolved to form a 0.1 mol / L solution. Dissolve 4.93 g of 2-methylimidazole in 100 ml of anhydrous methanol and shake until completely dissolved. Then slowly pour the 2-methylimidazole solution into the cobalt nitrate solution. After stirring at 25 °C for 1 h, collect the resulting milky suspension and centrifuge it at 8000 rpm for 10 min. Wash the centrifuged white precipitate with methanol three times and dry it in an oven at 70 °C overnight to obtain ZIF-67. Next, add 0.448 g of POTS to 40 ml of ethanol and stir for 2 h. Add 0.196 g of ZIF-67 powder and stir for 30 min. After ultrasonic treatment for 40 min, obtain the ZIF-67 / POTS superhydrophobic coating solution. Finally, soak the PVDF substrate membrane in ethanol for 2 h and dry it. Wet the spray gun with a small amount of methanol for pre-spraying. Pour the ZIF-67 / POTS superhydrophobic coating solution into the spray gun. Place the PVDF substrate membrane at an angle of 30° to the horizontal plane. The spray gun nozzle is perpendicular to the membrane and 15 cm away. The spraying speed is 0.5 mm / s. After each spraying, place the membrane in an oven at 70 °C for 15 min. Repeat three times to form the ZIF-67 / POTS superhydrophobic coating, and dry the membrane in an oven at 70 °C overnight.
[0068] Step 5: Synthesize the PVDF-ZIF-67 / POTS membrane by layer-by-layer assembly of the PVDF layer and the PVDF substrate membrane sprayed with the ZIF-67 / POTS superhydrophobic coating.
[0069] Respectively use the PVDF-ZIF-67 / POTS membrane of Comparative Example 2 and the PVDF substrate membrane prepared in Comparative Example 1 to simulate 500 mL of radioactive laundry wastewater containing 60 mg / L of sodium dodecyl sulfate, 200 mg / L of machine oil, 100 mg / L of sodium oleate, and 10 mg / L of uranium in a nuclear power plant. Use it as the feed liquid and conduct a membrane distillation experiment according to the method of Application Example 2. Measure the rejection rate of the PVDF substrate membrane and measure the membrane flux and conductivity of the PVDF-ZIF-67 / POTS membrane. The test results are as Figure 8 shown.
[0070] The results show that during the treatment of radioactive laundry wastewater containing 60 mg / L of sodium dodecyl sulfate, 200 mg / L of machine oil, 100 mg / L of sodium oleate, and 10 mg / L of uranium in a nuclear power plant, the membrane flux of the PVDF-ZIF-67 / POTS membrane is lower than that of the PVDF-Q-ZIF-67 / POTS membrane, and the conductivity increases, indicating that the PVDF-Q-ZIF-67 / POTS membrane is more suitable for treating radioactive laundry wastewater and has excellent anti-wetting performance.
[0071] Figure 9This is the comparison chart of nuclide rejection rates in Application Example 2 and Comparative Example 2 of the present invention. It can be seen from Figure 9 that the PVDF-Q-ZIF-67 / POTS membrane prepared by introducing quercetin (Que) in the present invention has a significantly higher nuclide rejection rate for low-level radioactive waste liquid than the PVDF base membrane and the PVDF-ZIF-67 / POTS membrane without introducing quercetin (Que).
[0072] Comparative Example 3 (different from Example 1 in that: the superhydrophobic layer is different, and the others are carried out according to Example 1 to obtain the PVDF-Q-SiO 2 membrane)
[0073] Step 1: Dissolve 22 g of PVDF in a beaker containing 178 g of DMAC, and magnetically stir at 400 r / min at 60 °C for 2 h until completely dissolved to obtain a PVDF solution; place 1 g of PVA and 0.2 g of Que in 5.47 g of DMSO, and magnetically stir at 400 r / min at 60 °C for 2 h until completely dissolved to obtain a PVA solution; mix the PVDF solution and the PVA solution, and magnetically stir at 400 r / min at 60 °C for 2 h, and obtain a PVDF-Q hydrophilic layer by electrospinning. Place the PVDF-Q hydrophilic bottom layer in an oven at 60 °C and dry for 1 h.
[0074] Step 2: Mix 1.2 g of GA, 4.8 g of CA, and 394 g of deionized water to form a mixed solution, then immerse the PVDF-Q hydrophilic layer in the mixed solution and crosslink for 2 h, then rinse 3 times with deionized water, and place it in an oven at 60 °C and dry for 1 h.
[0075] Step 3: Dissolve 0.2 g of LiCl in 177.8 g of DMAC, then add 22 g of PVDF, and magnetically stir at 400 r / min at 60 °C for 2 h until completely dissolved, let it stand for defoaming to form a spinning solution, and obtain a PVDF base membrane by electrospinning. The conditions for electrospinning are: voltage -2.4 / 14.5 KV, the distance from the metal needle of the syringe to the electrospinning drum is 16 cm, the drum rotation speed is 30 r / min, the injection speed is 0.15 mm / min, the temperature is 27 °C, and the translation range is 120 cm.
[0076] Step 4: Prepare an electrospinning solution. First, mix 94.8 g of DMAC and 94.8 g of THF, add 0.4 g of SiO 2 particles (with a diameter of 500 nm), perform ultrasonic water bath treatment for 30 min, then add 6 g of PDMS, perform ultrasonic treatment for 30 min, then stir at 60 °C for 2 h, and finally add 4 g of PVDF and stir at 60 °C for 2 h until completely dissolved to obtain an electrospinning solution; then electrostatically spray the electrospinning solution on the surface of the PVDF base membrane to form PDMS / PVDF-SiO2 Three-dimensional superhydrophobic microsphere layer.
[0077] Step Five: The PVDF-Q hydrophilic layer and the PVDF-based membrane sprayed with PDMS / PVDF-SiO 2 Three-dimensional superhydrophobic microsphere layer, and the PVDF-Q-SiO membrane is synthesized by layer-by-layer assembly. 2 Membrane.
[0078] Using the PVDF-Q-SiO 2 membrane, 500 mL of radioactive waste liquid containing 0.01 mol / L oxalic acid, 0.005 mol / L citric acid, 1 g / L potassium permanganate, 10 mg / L strontium, and 10 mg / L cobalt in a nuclear power plant is used as the feed liquid, and the membrane distillation experiment is carried out according to the method of Application Example 1, and the membrane flux, rejection rate, and conductivity are measured. The test results are as Figure 10 shown.
[0079] The results show that during the process of treating the radioactive waste liquid containing 0.01 mol / L oxalic acid, 0.005 mol / L citric acid, 1 g / L potassium permanganate, 10 mg / L strontium, and 10 mg / L cobalt in a nuclear power plant with the PVDF-Q-SiO 2 membrane, the membrane flux of the PVDF-Q-SiO 2 membrane is lower than that of the PVDF-Q-ZIF-67 / POTS membrane, indicating that the method of the ZIF-67 / POTS superhydrophobic coating can better improve the membrane flux.
[0080] Comparative Example 4 (different from Example 1 in that: the superhydrophobic layer is different, and the others are carried out according to Example 1, and the PVDF-Q-ZIF-67 / POTS / SiO 2 membrane is obtained)
[0081] Step One: Dissolve 22 g of PVDF in a beaker containing 178 g of DMAC, and stir magnetically at 400 r / min at 60 °C for 2 h until completely dissolved to obtain a PVDF solution; dissolve 1 g of PVA and 0.2 g of Que in 5.47 g of DMSO, and stir magnetically at 400 r / min at 60 °C for 2 h until completely dissolved to obtain a PVA solution; mix the two solutions of the PVDF solution and the PVA solution, stir magnetically at 400 r / min at 60 °C for 2 h, and obtain the PVDF-Q hydrophilic layer by electrospinning. Place the PVDF layer in an oven at 60 °C and dry for 1 h. Among them, the conditions for electrospinning are: voltage -2.4 / 20 KV, the distance from the metal needle tip of the syringe to the electrospinning roller is 20 cm, the roller rotation speed is 60 r / min, the injection speed is 0.1 mm / min, the temperature is 27 ± 3 °C, the translation range is 120 cm, the drying temperature is 60 °C, and the drying time is 1 h.
[0082] Step 2: Mix 1.2 g of GA, 4.8 g of CA, and 394 g of deionized water to form a mixed solution. Then immerse the PVDF layer in the mixed solution for crosslinking for 2 h, rinse it with deionized water 3 times, and dry it in an oven at 60 °C for 1 h.
[0083] Step 3: Dissolve 0.2 g of LiCl in 177.8 g of DMAC, then add 22 g of PVDF, and magnetically stir at 60 °C at 400 r / min for 2 h until completely dissolved. Let it stand for defoaming to form a spinning solution, and obtain a PVDF-based membrane after electrospinning. Among them, the conditions for electrospinning are: voltage -2.4 / 28 KV, the distance from the metal needle tip of the syringe to the electrospinning drum is 20 cm, the drum rotation speed is 60 r / min, the injection speed is 0.06 mm / min, the temperature is 27 ± 3 °C, and the translation range is 120 cm.
[0084] Step 4: Prepare a ZIF-67 / POTS / SiO 2 superhydrophobic coating solution. First, dissolve 2.91 g of cobalt nitrate hexahydrate in 100 ml of anhydrous methanol and shake until completely dissolved to form a 0.1 mol / L solution. Dissolve 4.93 g of 2-methylimidazole in 100 ml of anhydrous methanol and shake until completely dissolved. Then slowly pour the 2-methylimidazole solution into the cobalt nitrate solution, stir at 25 °C for 1 h, collect the resulting milky suspension, and centrifuge at 8000 rpm for 10 min. Wash the centrifuged white precipitate with methanol 3 times and dry it in an oven at 70 °C overnight to obtain ZIF-67; then add 0.448 g of POTS to 40 ml of ethanol and stir for 2 h, then add 0.196 g of ZIF-67 powder and 0.182 g of SiO 2 and stir for 30 min, and obtain a ZIF-67 / POTS / SiO 2 superhydrophobic coating solution after ultrasonic treatment for 40 min; finally, immerse the PVDF-based membrane in ethanol for 2 h and dry it. Wet the spray gun with a small amount of methanol for pre-spraying, pour the ZIF-67 / POTS / SiO 2 superhydrophobic coating solution into the spray gun, place the PVDF-based membrane at an angle of 30° to the horizontal plane, keep the spray gun nozzle perpendicular to the membrane and at a distance of 15 cm, the spraying speed is 0.5 mm / s, and place the membrane in an oven at 70 °C for 15 min after each spraying. Repeat 3 times to form a ZIF-67 / POTS / SiO 2 superhydrophobic coating, and place the membrane in an oven at 70 °C to dry overnight.
[0085] Step 5: Assemble the PVDF-Q hydrophilic layer and the PVDF-based membrane sprayed with the ZIF-67 / POTS / SiO 2 superhydrophobic coating layer by layer to synthesize a PVDF-Q-ZIF-67 / POTS / SiO 2 membrane.
[0086] Using PVDF-Q-ZIF-67 / POTS / SiO 2 membrane, 500 mL of radioactive laundry wastewater containing 60 mg / L sodium dodecyl sulfate, 200 mg / L machine oil, 100 mg / L sodium oleate, and 10 mg / L uranium in a nuclear power plant was simulated as the feed liquid. The membrane distillation experiment was carried out according to the method of Application Example 2, and the membrane flux and rejection rate were measured. The test results are as Figure 11 shown.
[0087] The results show that during the process of treating radioactive laundry wastewater containing 60 mg / L sodium dodecyl sulfate, 200 mg / L machine oil, 100 mg / L sodium oleate, and 10 mg / L uranium in a nuclear power plant with the PVDF-Q-ZIF-67 / POTS / SiO 2 membrane, the membrane flux was lower than that of the PVDF-Q-ZIF-67 / POTS membrane at the initial stage. After a period of time, the membrane fluxes of the two were basically the same. It is speculated that the addition of SiO 2 would block the membrane pores, resulting in a decrease in membrane flux, and SiO 2 could not exist stably for a long time, so the membrane flux increased. This indicates that the PVDF-Q-ZIF-67 / POTS membrane has better anti-wetting performance than the PVDF-ZIF-67 / POTS / SiO 2 membrane and is more suitable for treating radioactive laundry wastewater.
[0088] Comparative Example 5 (different from Example 1 in that the superhydrophobic layer is different, and the others are carried out according to Example 1 to obtain a PVDF-Q-ZIF-67 membrane)
[0089] Step 1: Dissolve 22 g of PVDF in a beaker containing 178 g of DMAC, and stir magnetically at 400 r / min at 60 °C for 2 h until completely dissolved to obtain a PVDF solution; dissolve 1 g of PVA and 0.2 g of Que in 5.47 g of DMSO, and stir magnetically at 400 r / min at 60 °C for 2 h until completely dissolved to obtain a PVA solution; mix the two solutions of the PVDF solution and the PVA solution, stir magnetically at 400 r / min at 60 °C for 2 h, and obtain a PVDF-Q hydrophilic layer by electrospinning. Place the PVDF layer in a drying oven at 60 °C for 1 h. Among them, the conditions for electrospinning are: voltage -2.4 / 20 KV, the distance from the metal needle tip of the syringe to the electrospinning roller is 20 cm, the roller speed is 60 r / min, the injection speed is 0.1 mm / min, the temperature is 27 ± 3 °C, the translation range is 120 cm, the drying temperature is 60 °C, and the drying time is 1 h.
[0090] Step 2: Mix 1.2 g of GA, 4.8 g of CA, and 394 g of deionized water to form a mixed solution. Then immerse the PVDF layer in the mixed solution for crosslinking for 2 h, rinse it with deionized water three times, and dry it in an oven at 60 °C for 1 h.
[0091] Step 3: Dissolve 0.2 g of LiCl in 177.8 g of DMAC, then add 22 g of PVDF, and magnetically stir at 60 °C at 400 r / min for 2 h until completely dissolved. Let it stand for degassing to form a spinning solution, and obtain a PVDF-based membrane after electrospinning. Among them, the conditions for electrospinning are: voltage -2.4 / 28 KV, the distance from the metal needle of the syringe to the electrospinning roller is 20 cm, the roller speed is 60 r / min, the injection speed is 0.06 mm / min, the temperature is 27 ± 3 °C, and the translation range is 120 cm.
[0092] Step 4: Prepare a ZIF-67 superhydrophobic coating solution. First, dissolve 2.91 g of cobalt nitrate hexahydrate in 100 ml of anhydrous methanol and shake until completely dissolved to form a 0.1 mol / L solution. Dissolve 4.93 g of 2-methylimidazole in 100 ml of anhydrous methanol and shake until completely dissolved. Then slowly pour the 2-methylimidazole solution into the cobalt nitrate solution, stir at 25 °C for 1 h, collect the resulting milky suspension, and centrifuge at 8000 rpm for 10 min. Wash the centrifuged white precipitate three times with methanol and dry it in an oven at 70 °C overnight to obtain ZIF-67. Add 0.196 g of ZIF-67 powder to 40 ml of ethanol and stir for 2 h, and obtain a ZIF-67 superhydrophobic coating solution after ultrasonic treatment for 40 min. Finally, immerse the PVDF-based membrane in ethanol for 2 h and dry it. Wet the spray gun with a small amount of methanol for pre-spraying. Pour the ZIF-67 superhydrophobic coating solution into the spray gun. Place the PVDF-based membrane at an angle of 30° to the horizontal plane. The spray gun nozzle is perpendicular to the membrane and the distance is 15 cm. The spraying speed is 0.5 mm / s. After each spraying, place the membrane in an oven at 70 °C for 15 min, repeat three times to form a ZIF-67 superhydrophobic coating, and dry the membrane in an oven at 70 °C overnight.
[0093] Step 5: Synthesize a PVDF-Q-ZIF-67 membrane by layer-by-layer assembly of the PVDF-Q hydrophilic layer and the PVDF-based membrane sprayed with the ZIF-67 superhydrophobic coating.
[0094] Use the PVDF-Q-ZIF-67 membrane to simulate 500 mL of radioactive laundry wastewater containing 60 mg / L of sodium dodecyl sulfate, 200 mg / L of engine oil, 100 mg / L of sodium oleate, and 10 mg / L of uranium in a nuclear power plant as the feed liquid, and conduct a membrane distillation experiment according to the method of Application Example 2, measure the membrane flux and rejection rate, and the test results are as Figure 12 shown.
[0095] The results show that during the process of treating radioactive laundry wastewater containing 60 mg / L sodium dodecyl sulfate, 200 mg / L machine oil, 100 mg / L sodium oleate, and 10 mg / L uranium in nuclear power plants with the PVDF-Q-ZIF-67 membrane, its membrane flux gradually decreases after a period of time, lower than that of the PVDF-ZIF-67 / POTS membrane during long-term operation, and the nuclide rejection rate of the PVDF-Q-ZIF-67 membrane is lower than that of the PVDF-Q-ZIF-67 / POTS membrane, indicating that the addition of POTS enhances the anti-wetting performance of the membrane.
[0096] In the present invention, a PVDF-Q hydrophilic layer is obtained by electrospinning a blend of PVA material, Que, and PVDF powder. Then, a PVDF-based membrane is obtained by electrospinning a blend of LiCl and PVDF. Subsequently, a ZIF-67 / POTS superhydrophobic coating is sprayed on the PVDF-based membrane using ZIF-67 and POTS as raw materials, and the PVDF-Q-ZIF-67 / POTS membrane is synthesized by layer-by-layer assembly, improving the membrane flux and mechanical properties. The PVDF-Q-ZIF-67 / POTS membrane is used for direct contact membrane distillation of two types of radioactive waste liquids in nuclear power plants, which can effectively separate the nuclides in the radioactive waste liquid and maintain a stable membrane flux, and also helps to a certain extent in the enrichment of uranium.
[0097] Although the embodiments of the present invention have been disclosed as above, it is not limited to only the applications listed in the specification and embodiments. It can be fully applied to various fields suitable for the present invention. For those familiar with the field, additional modifications can be easily made. Therefore, without departing from the general concept defined by the claims and the equivalent scope, the present invention is not limited to the specific details and the examples shown and described herein.
Claims
1. A method for preparing a PVDF-Q-ZIF-67 / POTS membrane, characterized in that: The following steps are involved: Step 1, placing polyvinylidene fluoride in dimethylacetamide, stirring until completely dissolved, to obtain a polyvinylidene fluoride solution; dissolving polyvinyl alcohol and quercetin in dimethyl sulfoxide, stirring until completely dissolved, to obtain a polyvinyl alcohol solution, mixing the two solutions, stirring, and then electrospinning to obtain a polyvinylidene fluoride / polyvinyl alcohol / quercetin hydrophilic layer, and drying; Step 2, immersing the polyvinylidene fluoride / polyvinyl alcohol / quercetin hydrophilic layer in a mixed solution for cross-linking, and then rinsing with deionized water and drying; Step 3, dissolving LiCl in dimethylacetamide, then adding polyvinylidene fluoride, stirring until completely dissolved, standing to degas, forming a spinning solution, and obtaining a polyvinylidene fluoride film after electrostatic spinning; Step 4: prepare a ZIF-67 / 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane super-hydrophobic coating solution, and spray the solution on the surface of the polyvinylidene fluoride film using a spray gun to form a ZIF-67 / 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane super-hydrophobic coating; Step 5: The polyvinylidene fluoride / polyvinyl alcohol / quercetin hydrophilic layer and the polyvinylidene fluoride based membrane sprayed with a ZIF-67 / 1H,1H,2H,2H-perfluorooctyltriethoxysilane superhydrophobic coating are assembled layer by layer to synthesize a PVDF-Q-ZIF-67 / POTS membrane.
2. The method for preparing the PVDF-Q-ZIF-67 / POTS membrane according to claim 1, characterized in that: In the step 1, the mass of polyvinylidene fluoride accounts for 11-13wt% of the polyvinylidene fluoride solution system, the mass of dimethylacetamide accounts for 87-89wt% of the polyvinylidene fluoride solution system, the mass of polyvinyl alcohol accounts for 15-18wt% of the polyvinyl alcohol solution system, the mass of quercetin accounts for 3-8wt% of the polyvinyl alcohol solution system, and the mass of dimethyl sulfoxide accounts for 74-82wt% of the polyvinyl alcohol solution system.
3. The method for preparing the PVDF-Q-ZIF-67 / POTS membrane according to claim 1, characterized in that: In the step 1, magnetic stirring is used for stirring, the stirring speed is 400-600 r / min, the stirring temperature is 60-80° C., the mass ratio of the polyvinylidene fluoride solution to the polyvinyl alcohol solution is 6-7:3-4, and the stirring time is 2-4 h.
4. The method for preparing the PVDF-Q-ZIF-67 / POTS membrane according to claim 1, characterized in that: In the step 1, the conditions for electrospinning are: voltage -2.4 / 20KV, the distance from the metal needle of the needle tube to the electrospinning drum is 20-24cm, the drum speed is 60-80r / min, the injection speed is 0.1-0.2mm / min, the temperature is 27±3°C, the translation range is 120cm, the drying temperature is 60-80°C, and the drying time is 1h.
5. The method for preparing the PVDF-Q-ZIF-67 / POTS membrane according to claim 1, characterized in that: In the step 2, the mixed solution is prepared by mixing 25% glutaraldehyde solution, citric acid and deionized water in a mass ratio of 0.1-0.3:1.2-1.3:96.5-98.5, the crosslinking time is 2 hours, and the deionized water is rinsed 2-3 times; the drying oven temperature is 60-80°C, and the drying time is 1-2 hours.
6. The method for preparing the PVDF-Q-ZIF-67 / POTS membrane according to claim 1, characterized in that: In the step 3, the mass of LiCl accounts for 0.1-0.2wt% of the entire solution system, the mass of polyvinylidene fluoride accounts for 10-11wt% of the entire solution system, and the mass of dimethylacetamide accounts for 88.8-88.9wt% of the entire solution system. Magnetic stirring is adopted, the stirring speed is 400-800r / min, and the stirring temperature is 60-70°C.
7. The method for preparing the PVDF-Q-ZIF-67 / POTS membrane according to claim 1, characterized in that: In the step 3, the conditions for electrospinning are: voltage -2.4 / 28KV, distance from the metal needle of the needle tube to the electrospinning drum is 20-24cm, drum speed is 60-80r / min, injection speed is 0.06-0.1mm / min, temperature is 27±3°C, and translation range is 120cm.
8. The method for preparing the PVDF-Q-ZIF-67 / POTS membrane according to claim 1, characterized in that: In the step 4, the preparation method of the ZIF-67 / 1H, 1H, 2H, 2H-perfluorooctyl triethoxysilane super hydrophobic coating solution is as follows: dissolving cobalt nitrate hexahydrate in anhydrous methanol and shaking until completely dissolved to form a 0.1 mol / L solution, dissolving 2-methylimidazole in anhydrous methanol and shaking until completely dissolved to prepare a 0.4-0.6 mol / L solution, and then slowly pouring the 2-methylimidazole solution into the cobalt nitrate solution according to a molar ratio of cobalt ions to 2-methylimidazole of 1:4-6, collecting the resulting emulsion suspension after stirring at 25°C for 1 hour, and precipitating at 8000-1000 ℃. 00rpm for 8-10min, wash the white precipitate obtained by centrifugation with methanol three times, and dry it in an oven at 70-80℃ overnight to obtain ZIF-67 powder; add 1H,1H,2H,2H-perfluorooctyltriethoxysilane to 40ml ethanol and stir for 2h, add ZIF-67 powder and stir for 30min, the molar ratio of ZIF-67 to 1H,1H,2H,2H-perfluorooctyltriethoxysilane is 1:1, and after ultrasonication for 40min, a ZIF-67 / 1H,1H,2H,2H-perfluorooctyltriethoxysilane superhydrophobic coating solution is obtained.
9. The method for preparing the PVDF-Q-ZIF-67 / POTS membrane according to claim 1, characterized in that: In the step 4, the conditions for spraying the prepared solution are as follows: the polyvinyl fluoride film is immersed in ethanol for 2 hours and dried, the spray gun is moistened with a small amount of methanol for pre-spraying, the polyvinyl fluoride film is placed at an angle of 30° to the horizontal plane, the spray gun nozzle is perpendicular to the film and the distance is 15 cm, the spraying speed is 0.5 mm / s, and after each spraying, the film is placed in a 70°C oven for 15 minutes, repeated 3 times, and finally the film is placed in a 70°C oven to dry overnight.
10. An application of a PVDF-Q-ZIF-67 / POTS membrane prepared by the preparation method according to any one of claims 1 to 9 in treating radioactive waste liquid from a nuclear power plant, characterized in that: The specific method is as follows: the radioactive waste liquid is pumped into a direct contact membrane distillation device using a PVDF-Q-ZIF-67 / POTS membrane to perform membrane distillation, the temperature difference between the two sides of the membrane material is used as a driving force to obtain a concentrated liquid, and the distillate is condensed and collected to complete the concentration of the radioactive waste water and the separation of nuclides. In the direct contact membrane distillation device, the feed temperature of the radioactive waste liquid is set to 70-80°C, the feed and discharge flow rates are 100rpm, the permeate is 200ml of pure water, and the condensation temperature is 25°C; the radioactive waste liquid is heated from room temperature to the feed temperature required for membrane distillation, the heat energy comes from the waste heat utilization system of the nuclear power plant reactor, and the recovery method is one of a heat pump, a regenerator, and a heating furnace, and no additional heating is required.
Citation Information
Cited By
Gas sensitive material based on PVDF / ZIF-8 composite nanofiber membrane as well as preparation method and application of gas sensitive material
CN121653957A